PERTUMBUHAN DAN HASIL SELADA PADA BERBAGAI KOMPOSISI MEDIA TANAM DENGAN PEMBERIAN URIN KAMBING - Ni Made Titiaryanti; Titin Setyorini; Siti Yuli Meilinda Sormin (AGROISTA : Jurnal Agroteknologi, 2018)
Lettuce is a type of vegetables that are favored by Indonesian. Lettuce is usually served as fresh vegetables. The leaves contain of vitamin A, vitamin B, and vitamin C. The research aims to determine the effect of various compositions growing medium with addition of goat urine on growth and yield of lettuce. The research was conducted in Maguwoharjo Yogyakarta, from November 2016 to January 2017. Completely Randomized Design (CRD) factorial consisting of two factors was applied as experimental design. The first factor was growing media consisting of four levels, namely M1 (soil), M2 (soil+compost), M3 (soil+charcoal rice husk), M4 (soil+compost+charcoal rice husk). The second factor was dosage of goat urine consisting of four levels, namely D0 (0 ml, NPK was applied), D1 (50 ml), D2 (100 ml), and D3 (150 ml). Analysis of variance (ANOVA) and Least Significance Difference (LSD), both with significance level of 5%, were then used to find out whether significant differences among treatments, were existed. The result showed that there was an interaction between treatments in plant height. The best combination was M3 (soil+charcoal rice husk) and D0 (0 ml/NPK). The compositions of growing media were significantly affected in number of leaves, fresh weight of plant, and fresh weight of upper part of plant. The best growing medium was M2 (soil+compost). The application of goat urine showed the same effect on growth and yield of lettuce. Goat urine can replace NPK (plant fertilizer) on growth and yield of lettuce. Keywords: Growth and yield, lettuce, growing medium, goat urine